Water Quality of the Koto Panjang Dam based on Physical-Chemical Parameters and Saprobic Coefficient (X) - Maulana, Rezki; Fajri, Nur El; ', Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
In the Koto Panjang Dam, the water quality is affected by pollutant input originated from activities conducted around and in the dam, such as illegal logging, boat activities, households and floating net cage fish culture. To understand the water quality in general, a research was conducted from January 2016. This research aims to determine the water quality of the reservoir based on physical, chemical parameters and saphrobic coefficient (X). There were three stations, 3 sampling points/ station. Water samples were taken 3 times/ week. Water quality parameters measured were water temperature, turbidity, brightness, TSS, pH, DO, BOD5, nitrate and phosphate. While plankton were identified based on Yunfang (1995) and Hiroyuki (1977). Results shown that there were 7 classes of plankton present, namely Cyanophyceae (7 genus), Chlorophyceae (8 genus), Bacillariophyceae (8 genus), Dinophyceae (1 genus), Euglenophyceae (2 genus), Rotifer (1 genus) and Ciliate (1 genus). Water quality parameters are as follows: temperature : 29 – 30 0C, turbidity: 1.6 – 2.7 NTU, brightness : 120 – 145,5 cm, TSS : 26 – 42 mg/L, pH 5 – 6, DO : 5.3 – 6 mg/L, BOD5 : 3.2 – 3.62 mg/L, nitrate : 0.058 – 0.065 mg/L and phosphate : 0.030 – 0.039 mg/L. The saphrobic coefficient (X) of the water was 0.71-0.80 and it means that the Koto Panjang Dam is lightly polluted (mesosaphrobic phase).Keywords : Koto Panjang Dam, fish cage, mesosaphrobic phase, Saphrobic Coefficent